Potential Feature of Combined AB5-Type Metal Hydride Tank and PEMFC as a Safer System for Hydrogen Fueling in Bangladesh - Salam, Md Abdus; Islam, Thauhidul; Ahmed, Kawsar; Sahab uddin, Md; Habib, Shehan; Abdullah, Bawadi (Frontiers in Energy Research, 2021)
Metal hydrides are very much reported a potential, safe option for high density hydrogen storage materials. A combined system of a PEMFC and metal hydride (MH) tanks is designed to investigate their characteristics and performances as hydrogen storage and stable power supply system. AB5 type (LaCe)Ni5 material containing three (3) MH tanks are selected for investigation. Endothermic dehydrogenation of metal hydride controls the hydrogen evolution rates during discharging period that reduce the risk of accidents. The MH tank that charged at 20 0C water bath sustain and supply hydrogen for the longer time of 240 minutes. The performances of the MH tank at water bath of 20 oC and 10 bar conditions correspond that the optimum condition of the hydrogen storage of MH tank of Pragma. The performances of the combined system were investigated in different working conditions. The system sustains and supply hydrogen to PEMFC for 240, 160, 130 & 110 minutes for the working load of 250 W, 500 W, 1000 W & 2000 W accordingly. It is concluded that hydrogen consumption frequency increases for higher load demand.